Soil structure quality indicators and their limit values. (September 2019) - Johannes, Alice; Weisskopf, Peter; Schulin, Rainer; Boivin, Pascal
Highlights: Structural porosity and gravimetric air content are indicators of structure quality. Gravimetric air content is the best simple, inexpensive and accessible indicator. Target, trigger and remediation values for environmental legislation are provided. Visual evaluation of soil structure was used as independent classification scheme. More than 90% of the samples were correctly classed. Abstract: Most soil functions, such as food production, carbon and nutrient cycling or water regulation and filtration strongly depend on soil structure quality (SSQ). But SSQ is increasingly threatened by compaction, carbon loss and erosion. SSQ should be protected by environmental regulations, however, reliable and easy methods for SSQ assessment are still missing. The aim of this study was to define a classification scheme and its indicators for soil structure protection regulation. Therefore, the physical properties of soil samples were determined with shrinkage analysis and their structure quality was scored with CoreVESS to provide a classification scheme independent from the indicators. We collected 185 undisturbed samples from the A horizon of Cambi-Luvisols across western Switzerland. CoreVESS score (Sq) 2 was used to identify the target value corresponding to good structure quality. Sq 3 was used to identify the trigger value, i.e. the limit between good and poor SSQ. Sq 4 was used to identify the remediation value. We found that structural porosity and gravimetric air content at −100 hPa (A−100 ) determined on undisturbed samples equilibrated free to swell in the laboratory were the best suited parameter to assess SSQ. They were correlated to SOC for soils with good SSQ, but not for soils with poor SSQ. As SOC was highly correlated to gravimetric water content at −100 hPa (W−100 ), it was possible to approximate SOC by W−100 in order to simplify the method for application. A−100 and W−100 are easy and inexpensive to determine and are therefore proposed as indicators. The limit values of A−100 were identified as following: target is 0.023 + 0.288 W−100 cm 3 g −1, trigger is 0.068 cm 3 g −1 and remediation is 0.045 cm 3 g −1 . These values were designed to be useful to the Swiss environmental law. They apply to the Cambi-luvisol A horizons, and their applicability to subsoil or other soil types should be further studied.